ANALISI RISIKO KESEHATAN PAJANAN BENZENE PADA PEKERJA DI LABORATORIUM PT X - Dewi Nata Rina; Sutrani Rachmawati (Universitas Pahlawan, 2022)
The laboratory is a work area that has various kinds of hazards, such as benzene exposure which has a health risk for workers. This study aims to analyze the health risks caused by benzene exposure to workers in the PT X laboratory. This study used a cross-sectional design with a descriptive approach which was carried out in the Liquefied Natural Gas testing laboratory of PT X. The study used the Chemical Health Risk Assessment (CHRA) Department of Occupational Safety and Health (DOSH)Malaysia method. 3 workers have a moderate level of risk and 1 worker has a high level of risk, where high exposure can cause carcinogenic effects. The air ventilation sistem as a risk control does not function optimally. The level of risk of benzene exposure to workers through inhalation is at moderate and high levels. It is necessary to improve the air ventilation sistem to reduce the exposure to the dangers of benzene in workers. Keywords : Health Risk Analysis, Benzene, Laboratory